ANALISIS TINDAK PIDANA PENCUCIAN UANG MELALUI JUDI ONLINE: STUDI PUTUSAN NOMOR 1018/PID/2023/PT MDN - Himawan, Nanda Rafi; Zulfiani, Anita (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
This research is presented to study and understand the criminal law regulations for the crime of money laundering through online gambling which is currently widespread by conducting a study of the Medan High Court decision Number 1018/PID/2023/PT MDN. This research is normative research with a perspective using an approach through statutory regulations and real cases. In this research, the types of data used are secondary data materials and primary data materials. Therefore, the technique for preparing this article is through literature study. The data analysis technique used in this writing is the deduction method using the major premise which is regulated in the money laundering criminal regulations Article 3, Article 4 and Article 5 of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Crimes. Washing and through other related regulations. In this decision, the defendant Jonni Alias Apin BK had committed the crime of money laundering as a participant